Effect of Planting Dates and GA3 Concentrations On Growth and Active Material of Chamomilla (Matricaria Chamomilla L.) Plants. - Al- Kaisi, W.A.; Nasr Allha, A.Y-; Bashi, R.W.; Hussan, A.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Experiment was conducted during the fall of 2002-2003 at the botanical gardenor of biology Department, Ibn- Al Hiatham Education college Baghdad University to study the effect of two planting dates (23/10 and 6/ll 2002) with different concentrations of GA3 (100 and 200 ppm) on growth characters and the active material of two cultivars (Local and German) of chamomilla (Matricaria chamomilla L.) plants. Randomized complete Block Design (R.C.B.D.) was used with three replications . Each one of the experiment units 1x1m .The parameters study were plant height, no shoots, no inflorescence branches and nodes , leaf area and leaf area index and violate oil percentage. The result showed that planting date. At 23/10 give a significant effect on all parameters which were used in comparison with planting on 6/11. GA3 at 100ppm on poth planting on date’s comparison with control treatment caused a significant result. German cultivar givesignificant results in comparison with local cultivar in all characters which were studied specially on planting date 23/10 of GA3 at 100 ppm.